Compliance with a structured bedside handover protocol: An observational, multicentred study. (August 2018) - Malfait, S.; Eeckloo, K.; Van Biesen, W.; Deryckere, M.; Lust, E.; Van Hecke, A.
Abstract: Background: Bedside handover is the delivery of the nurse-to-nurse shift handover at the patient's bedside. The method is increasingly used in nursing, but the evidence concerning the implementation process and compliance to the method is limited. Objectives: To determine the compliance with a structured bedside handover protocol following ISBARR and if there were differences in compliance between wards. Design: A multicentred observational study with unannounced and non-participatory observations (n = 638) one month after the implementation of a structured bedside handover protocol. Settings and participants: Observations of individual patient handovers between nurses from the morning shift and the afternoon shift in 12 nursing wards in seven hospitals in Flanders, Belgium. Methods: A tailored and structured bedside handover protocol following ISBARR was developed, and nurses were trained accordingly. One month after implementation, a minimum of 50 observations were performed with a checklist, in each participating ward. To enhance reliability, 20% of the observations were conducted by two researchers, and inter-rater agreement was calculated. Data were analysed using descriptive statistics, one-way ANOVAs and multilevel analysis. Results: Average compliance rates to the structured content protocol during bedside handovers were high (83.63%; SD 11.44%), and length of stay, the type of ward and the nursing care model were influencing contextual factors. Items that were most often omitted included identification of the patient (46.27%), the introduction of nurses (36.51%), hand hygiene (35.89%), actively involving the patient (34.44%), and using the call light (21.37%). Items concerning the exchange of clinical information (e.g., test results, reason for admittance, diagnoses) were omitted less (8.09%–1.45%). Absence of the patients (27.29%) and staffing issues (26.70%) accounted for more than half of the non-executed bedside handovers. On average, a bedside handover took 146 s per patient. Conclusions: When the bedside handover was delivered, compliance to the structured content was high, indicating that the execution of a bedside handover is a feasible step for nurses. The compliance rate was influenced by the patient's length of stay, the nursing care model and the type of ward, but their influence was limited. Future implementation projects on bedside handover should focus sufficiently on standard hospital procedures and patient involvement. According to the nurses, there was however a high number of situations where bedside handovers could not be delivered, perhaps indicating a reluctance in practice to use bedside handovers.